2008
DOI: 10.1021/jf703625r
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment and Quantitative Analysis of Flavonoids from Tea Samples of Different Origins by HPLC-DAD-ESI-MS

Abstract: Components of green tea ( Camellia sinensis) have been of considerable interest in recent years because of their potential utility as pharmaceutical agents, particularly for their antioxidant and anticarcinogenic activity. Responding to the increasing scientific validation of numerous health benefits of tea, a comprehensive approach was adopted to carry out analysis for the quality assessment of flavonoids in tea samples of different origins. For this purpose, extraction, separation, and mass spectrometric par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…In this regard, EGC was the main flavan-3-ol found in most samples; the highest concentration of individual flavan-3-ols was found in sample WT2, which is a blend of tea (white, green, and red tea). The second major compound found in the samples was EGCG in most cases, although it was not possible to determine a clear trend for flavan-3-ols due Sultana et al (2008) in green tea where high concentrations of EGCG and EGC were reported. EGCG levels ranged between 20.3 and 42.6 mg/g and EGC levels between 19.0 and 34.6 mg/g.…”
Section: Distribution Patterns Of Unfermented Teamentioning
confidence: 90%
See 1 more Smart Citation
“…In this regard, EGC was the main flavan-3-ol found in most samples; the highest concentration of individual flavan-3-ols was found in sample WT2, which is a blend of tea (white, green, and red tea). The second major compound found in the samples was EGCG in most cases, although it was not possible to determine a clear trend for flavan-3-ols due Sultana et al (2008) in green tea where high concentrations of EGCG and EGC were reported. EGCG levels ranged between 20.3 and 42.6 mg/g and EGC levels between 19.0 and 34.6 mg/g.…”
Section: Distribution Patterns Of Unfermented Teamentioning
confidence: 90%
“…In another study, the main flavan-3-ol occurring in 14 different tea samples was also EGC, where its concentration ranged from 8.0 mg/g to 83.3 mg/g, depending of the type of tea and cultivation site (Lin et al 2003). Altogether, differences in the reported levels can be attributed to variety, cultivation site, processing conditions and to the analytical methodology used for the determination of present phytochemicals; the concentration in the final extract was reported to be different depending on extraction conditions (Sultana et al 2008). Since compounds have different polarity and because they are subjected to different interactions in the sample matrix, one solvent may be effective for the extraction of one class of compounds and need not be effective to others.…”
Section: Distribution Patterns Of Unfermented Teamentioning
confidence: 96%
“…Qualitative and quantitative evaluation of the chemical constituents is vital for establishing the quality control profile and standardization of herbal extracts [1][2][3][4][5][6]. This makes a base for the investigation of metabolites which have various biological and pharmacological importance [1,4,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The current interest in the health eff ects of green tea has stimulated the development of new processes for the extraction of the polyphenolic fraction (Gulati et al, 2003;Pan et al, 2003;Sultana et al, 2008). Indeed, the quality of polyphenol extracts and their antioxidant activity depend not only on the quality of the starting material (geographic origin, climatic conditions, harvesting date, storage conditions), but also on the technological processes involved in its manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…Using microwaves, fully reproducible extractions could be completed in minutes, thereby leading to reduced solvent and energy consumption, simplifi ed manipulation and work-up, higher purity of the fi nal product and eliminating the post-treatment of waste water. Several classes of natural products such as essential oils (Lucchesi et al, 2004), bioactive compounds from herbs (Hao et al, 2002), GTPs and caff eine (Gulati et al, 2003;Pan et al, 2003;Sultana et al, 2008) as well as environmental contaminants (Vidal et al, 2007) have been effi ciently extracted from a variety of matrices.…”
Section: Introductionmentioning
confidence: 99%